Exploring the beneficial effects and possible mechanisms of repeated episodes of whole-body hypoxic perconditioning in rat model of preeclampsia - Yan Li; Chunyun Wang; Jing Wang; Leisi Tao (Hypertension in Pregnancy, 2020)
Aim The study explored the beneficial effects of repeated episodes of whole body hypoxic perconditioning (WHPC) on preeclampsia (PE)-like symptoms in rats. Material and Methods PE was induced by administration of L-NAME (75 mg/kg) and WHPC was performed by exposing rats to low O2 (8%) and normal O2 of 10 min each in four alternate cycles. Results L-NAME induced PE like symptoms in rats along with a decrease in the cystathionine-β-synthase (CBS) activity in the placental tissue, plasma levels of H2S and NO metabolites in pregnant rats. Two (GD9, GD14) and three episodes (GD9, GD14 and GD18) of WHPC improved PE-like symptoms with an increase in CBS activity and H2S levels. CBS inhibitor, amino-oxyacetic acid abolished the beneficial effects of three episodes of WHPC; while H2S donor, 4-methylbenzenecarbothioamide, 4-MBC attenuated PE-like symptoms. Conclusion WHPC attenuates L-NAME-induced PE-like symptoms due to increase in CBS activity and H2S-production.